If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -4(x + 2) * 2 + -3 Reorder the terms: y = -4(2 + x) * 2 + -3 Reorder the terms for easier multiplication: y = -4 * 2(2 + x) + -3 Multiply -4 * 2 y = -8(2 + x) + -3 y = (2 * -8 + x * -8) + -3 y = (-16 + -8x) + -3 Reorder the terms: y = -16 + -3 + -8x Combine like terms: -16 + -3 = -19 y = -19 + -8x Solving y = -19 + -8x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -19 + -8x
| 7(5m+8)=161 | | 2(4t+1)=42 | | 4(-1+1a)=-44 | | 6(5m+8)=78 | | 6(-2+7a)=-54 | | 2p+5=2 | | 3/4+1/3t=2/4 | | 4(4+w)=-4 | | 5(-6+6n)=180 | | 3(10+2d)=96 | | 6(3+2m)=-78 | | -4(-1)+2y=-8 | | 42=.5b(12) | | 6(1n-8)=12 | | 2(5t+6)=-18 | | -4(-2)+2y=-8 | | 4b^2+16b-48=0 | | 6(2m+4)=168 | | 6(9-4d)=-162 | | 4(-5a+5)=60 | | 6(3w+2)=66 | | 10s-5+3=4s+6 | | 5(-8-3a)=80 | | 2(6m-6)=-60 | | 2(9-5b)=-12 | | 3(7w-4)=-222 | | 5x(x+9)-7(x+9)= | | 5(2n-9)=-75 | | 4(10+7x)=124 | | 7(4-7t)=-462 | | 2(4a+6)=92 | | 6(2t-7)=-78 |